2009
DOI: 10.1159/000232160
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelationships between Abdominal Adiposity, Leptin and Bone Mineral Content in Overweight Latino Children

Abstract: Background/Aims: The link between abdominal fat and bone mineral content (BMC), independent of weight, has not been extensively studied. In Latino children, the contributions of abdominal subcutaneous and visceral fat to BMC have not been examined. Research on the effect of leptin on BMC has also been inconclusive. Methods: The present study included 256 overweight Latino children (111 girls, 145 boys; mean BMI 28.2; age 11.1 ± 1.7 years) from Los Angeles, California. Subcutaneous abdominal adipose tissue (SAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 46 publications
6
25
0
1
Order By: Relevance
“…It is important to note that hyperleptinemic state was found in the analyzed group, suggesting that leptin deficiency and/or resistance, as well as other proinflammatory adipokines involved in bone resorption may promote osteoporosis (22). Corroborating our findings, another study reported that both abdominal adipose tissue and leptin were negatively associated with BMC in Latino overweight children of both genders (36).…”
Section: Discussionsupporting
confidence: 79%
“…It is important to note that hyperleptinemic state was found in the analyzed group, suggesting that leptin deficiency and/or resistance, as well as other proinflammatory adipokines involved in bone resorption may promote osteoporosis (22). Corroborating our findings, another study reported that both abdominal adipose tissue and leptin were negatively associated with BMC in Latino overweight children of both genders (36).…”
Section: Discussionsupporting
confidence: 79%
“…The association between abdominal body fat and bone has also been explored in prepubertal [28,29] as well as in postpubertal [30,31] adolescents, and all studies suggest a negative association. The pediatric literature is currently unable to disentangle these conflicting results; existing studies have not always included both boys and girls [15,20,23,32], taken into account known determinants of bone health such as sexual maturity, physical activity and calcium intake [6,16,20,21], and some were limited by small sample sizes [6,16,23,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between fat and bone appears to be bone site specific and determined by regional rather than total body fat. Visceral fat may act as a pathogenic fat depot, whereas sc fat may exert protective effects on bone structure and strength in adults (52) but not in obese children (53). Whereas obesity appears to protect against hip and vertebral fractures, obese adults may be at increased risk of fracture at the humerus (54) and ankle (55,56).…”
mentioning
confidence: 99%